Evaluation of Hospital Management Information Sistem (HMIS) Implementation to Improve Service Quality at Mother and Child Hospital - Annisa Wahyuni; Nurhasanah Nasution; Riana Oktarina (International Journal of Health and Medicine, 2025)
The Hospital Management Information Sistem (SIMRS) is a key component in the digital transformation of healthcare services, aiming to enhance efficiency and service quality. This study evaluates the implementation of SIMRS at Mutiara Bunda Mother and Child Hospital and explores the challenges and opportunities for improvement. A qualitative case study approach was employed, with data collected through in-depth interviews, observations, and document reviews involving five key informants, including the medical records head, medical service manager, registration officers, and IT staff. The results show that the SIMRS covers registration, procedure input, laboratory, and pharmacy functions. However, issues such as delayed data entry by medical staff, limited equipment, lack of integration across service units, and absence of written user guidelines and regular training persist. The study concludes that although the SIMRS is in use at RSIA Mutiara Bunda, sistem optimization, staff capacity building, and stronger managerial support are crucial to fully realize its potential in improving service quality.